A PENERAPAN SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE PADA SISTEM PENDUKUNG PENJUALAN BATU SPLIT MENGGUNAKAN PHP DAN SQL - Ronaldo, Ronaldo; Sonita, Anisya (UNIVED Press, 2021)
Computerized Systems Can Help Speed Up The Completion Of Company Data Processing, With Technology Requiring That All Areas Of Work That Are Still Manual And Inefficient Can Be Done With Information Technology. The Simple Multi Attribute Rating Technique (SMART) Method Is A Multi-Criteria Decision Making Method Which Is Based On The Theory That Each Alternative Consists Of A Number Of Criteria That Have A Value And Each Criterion Has A Weight To Describe How Important Its Value Is Compared To Other Criteria. To Avoid The Risk Of Loss From The Business Undertaken, It Is Necessary To Review The Business Feasibility Study From Various Aspects. The Feasibility Study That The Author Will Carry Out Covers Six Aspects, Namely Legality, Environment, Market And Marketing, Technical And Technology, Management And Human Resources, And Finance. Can Provide Information On Stone Sales Using The Smart Method (Simple Multi Attribute Rating Technique) Based On 6 Aspects, Namely Legality, Environment, Market And Marketing, Technical And Technology, Management And Human Resources, And Finance.